2018
DOI: 10.1111/fwb.13175
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term persistence of freshwater mussel beds in labile river channels

Abstract: Freshwater mussels are among the world’s most imperilled species, and much effort has been expended to understand their precipitous decline. The current paradigm is that relative river bed stability over decades is critical to maintaining mussel beds at a given river reach. Such information, however, is in stark contrast to the fundamental understanding of self‐formed rivers. Here, we examine the relationship between long‐term occurrence of aggregated freshwater mussel communities (mussel beds) and the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 73 publications
4
24
0
Order By: Relevance
“…Thus, our results appear to provide validation of Sansom's et al. () hypothesis and a potential mechanistic understanding for how mussels are able to persist in habitats with varying levels of entrainment potential.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Thus, our results appear to provide validation of Sansom's et al. () hypothesis and a potential mechanistic understanding for how mussels are able to persist in habitats with varying levels of entrainment potential.…”
Section: Discussionsupporting
confidence: 81%
“…We show that species with certain morphologies (smooth and/or thin shells) plus demographic traits (i.e., short life spans, high fecundity, and high growth rates) were more associated with high RSS habitats than species that lacked these traits, which would suggest biological mechanisms for coping with high flows. Sansom et al (2018) examining persistence of mussel assemblages to bed load transport made a similar observation. The authors found that mussel beds within modeled rivers persisted over a 20-yr time span despite evidence that bed mobilization had occurred frequently (at least once every 2 yr or less) over that same time period.…”
Section: Principal Component Analysis: Integrating Life History Shelsupporting
confidence: 68%
See 2 more Smart Citations
“…Mussel larvae (glochidia) are obligate ectoparasites on fish (Barnhart, Haag, & Roston, ; Haag, ), and there is a strong positive relationship between mussel and fish diversity (Vaughn & Taylor, ). Mussels form dense, multispecies aggregations (mussel beds) in river reaches that are hydrologically stable (Sansom, Bennett, Atkinson, & Vaughn, ; Strayer, ), and these are often areas that become pool refugia as rivers dry. Thus, during droughts fishes are likely to be stranded in isolated pools with mussels.…”
Section: Introductionmentioning
confidence: 99%